Ibn al-Haytham's ground theory of distance perception. (September 2022) - Sedgwick, H. A.
The 11th-century Arab scholar, Ibn al-Haytham, in his Optics, offers a detailed, rigorous, empirically oriented explanation of distance perception that may be the first essentially modern, scientific theory of distance perception. Based on carefully described experiments, he argues that for distance to be perceived accurately: (1) the distance must lie along a continuous surface such as the ground; (2) the continuous surface must be visible; (3) the magnitudes of distances along the surface must be perceived and calibrated through bodily interaction (walking and reaching) with them; and finally (4) the distance must be moderate. Al-Haytham's work reached Europe early in the 13th century, and his was the dominant theory of distance perception there for about 400 years. It was superseded early in the 17th century by a theory, based on cues such as convergence and accommodation, of distance seen through empty, mathematized space. Around 1950, an explanation of distance perception strikingly like that of al-Haytham was independently developed by J. J. Gibson, who called his theory the "ground theory" of space perception.